Inhibition of coaggregation between Fusobacterium nucleatum and Porphyromonas (Bacteroides) gingivalis by lactose and related sugars. - Kolenbrander, P E (1989)
The coaggregation of Fusobacterium nucleatum PK1594 and Porphyromonas (Bacteroides) gingivalis PK1924 was inhibited equally well by lactose, N-acetyl-D-galactosamine, and D-galactose, which caused 50% inhibition of coaggregation at 2 mM sugar concentration. Other sugars such as D-galactosamine, D-fucose (6-deoxy-D-galactose), and alpha-methyl- and beta-methyl-D-galactosides also inhibited coaggregation. Sugar specificity was apparent, since neither L-fucose, L-rhamnose, N-acetyl-D-glucosamine, nor N-acetylneuraminic acid was an inhibitor. Protease treatment of the fusobacterium completely abolished coaggregation, whereas it had no effect on the coaggregating activity of the porphyromonad. Although numerous lactose-inhibitable coaggregating pairs are known to occur among gram-positive bacteria, this report and the accompanying survey (P. E. Kolenbrander, R. N. Andersen, and L. V. H. Moore, Infect. Immun. 57:3194-3203, 1989) are the first studies demonstrating the extensive nature of this type of interaction between gram-negative human oral bacteria. The significance of galactoside-inhibitable coaggregations between these two potential periodontal pathogens is discussed.